Simplification of sub-gap density of states extraction method for amorphous In-Ga-Zn-O thin-film transistors by a single capacitance-voltage curve. (April 2018) - Wang, Weiliang; Wang, Pengjun; Dai, Mingzhi
Abstract: Sub-gap density of states (DOS) is one of the key parameters which impact both the electrical characteristics and reliability of amorphous In-Ga-Zn-O (a-IGZO) thin-film transistors. So the investigation of DOS extraction is important. Here, a simplified and efficient DOS extraction method based on a single capacitance-voltage (C-V) curve is proposed. The method is verified by comparing with the results from the existing DOS extraction methods such as static current-voltage (I-V) measurement. Besides, this method is applied to extract DOS of an a-IGZO thin-film transistor with different electrical properties. This updated method is employed to explain the decrease of device turn-on voltage, which could be attributed to the DOS decrease. In summary, it is a simple method based on a single C-V curve without optical illumination, temperature dependence, accurate I-V model supporting or complicated mathematics fitting. Highlights: A simplified DOS extraction method based on a single C-V curve is proposed. The method need not accurate I-V model supporting or complicated mathematics fitting. The method is verified by comparing with the results from the existing methods.